The Buddha as Ender and Transformer of Lineages - Strong, John S. (Religions of South Asia, 2011)
This paper looks at three types of lineage in traditions about the Buddha. First, it traces the Buddha’s Śākya ancestry and shows how he puts an end to his genealogical lineage and transforms it into a Śākya monastic lineage. Second, it argues that the Buddha acts as a point of convergence for the synchronic lineage of his many past lives (Jātakas), and then as a dispersion point for the lineage of his many relics. Finally, it sees him as a pivotal figure in the ongoing lineage of Buddhas through the ages, past and present.